A theory of general ethics : human relationships, nature, and the built environment - Fox, Warwick (MIT, 2006)
An integrated approach to ethics that covers interhuman ethics, the ethics of the natural environment (including animals), and the ethics of the built environment, and enables us to offer sensible and defensible answers to the widest possible range of eth.